From autophagy to senescence and apoptosis in Angiotensin II‐treated vascular endothelial cells. Issue 10 (28th March 2014) - Shan, Haiyan; Guo, Dawei; Li, Xuelian; Zhao, Xin; Li, Wan; Bai, Xiaojuan
<x xml:space="preserve">Abstract</x> The aim of this study was to explore if cell autophagy is activated by AngII before aging using human umbilical vascular endothelial cells (HUVECs). The ultrastructural analysis of HUVECs was performed to observe autophagosomes. The LC3‐II/LC3‐I ratio was determined by western blot assay. The β‐gal staining was used to identify cell senescence. The flow cytometry was performed to evaluate cell apoptosis. The BH3 domain analog ABT737 or Beclin‐1 knockdown by specific shRNA or valsartan was applied to investigate their effects on cell autophagy, senescence, and apoptosis induced by Ang II. Cell autophagy was initiated after Ang II treatment at 24 h. And cell senescence and apoptosis were observed in Ang II‐treated cells at 48 h. The significant interaction of Beclin‐1 and Bcl‐2 was detected at 48 h after Ang II treatment. Beclin‐1 was indispensable to Ang II‐induced autophagy, and its BH3 domain was required for the interaction with Bcl‐2 to attenuate autophagy. Pretreated with valsartan, cells were present with less autophagic, senescent, and apoptotic cells after Ang II stimulation. In conclusion, Ang II induced autophagy, senescence, and apoptosis of HUVECs progressively, and autophagy presented an early protective effect on vascular endothelial damage due to Ang II.